2022
DOI: 10.1021/acs.langmuir.2c00526
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Leaflet Phospholipid Exchange Impacts the Ligand Density Available for Protein Binding at Supported Lipid Bilayers

Abstract: Phospholipid bilayers formed at solid−liquid interfaces have garnered interest as mimics of cell membranes to model association reactions of proteins with lipid bilayer-tethered ligands. Despite the importance of understanding how ligand density in a lipid bilayer impacts the protein−ligand association response, relating the ligand-modified lipid fraction to the absolute density of solution-accessible ligands in a lipid bilayer remains a challenge in interfacial quantitative analysis. In this work, confocal Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…While we estimated that 55% of the benzylguanine is accessible on the outer leaflet (see Supporting Information for calculation), previous studies have found that ~60% of ligands are accessible externally due to inter‐leaflet exchange. [ 18 ] Interestingly, we also achieved approximately 60% conjugation efficiency, which we assumed is the theoretical maximum conjugation efficiency. Lastly, we confirmed that liposomes conjugated with protein retained their size via DLS measurements.…”
Section: Resultsmentioning
confidence: 78%
“…While we estimated that 55% of the benzylguanine is accessible on the outer leaflet (see Supporting Information for calculation), previous studies have found that ~60% of ligands are accessible externally due to inter‐leaflet exchange. [ 18 ] Interestingly, we also achieved approximately 60% conjugation efficiency, which we assumed is the theoretical maximum conjugation efficiency. Lastly, we confirmed that liposomes conjugated with protein retained their size via DLS measurements.…”
Section: Resultsmentioning
confidence: 78%
“…In the present work, ∼ 30 nm pore-diameter silica provided adequate space for immobilizing DNA up to 30 bases in length. Silica particles with pore diameters as large as 100 nm are commercially available and have been employed in similar experiments to investigate protein binding to ligands at supported lipid bilayers. , Porous silica has a high surface energy that can lead to nonspecific adsorption, especially of proteins. Fortunately, there are numerous polyethylene glycol (PEG) reagents that can be used to backfill the areas between active DNA sites, greatly reducing nonspecific adsorption of protein targets to these surfaces .…”
Section: Discussionmentioning
confidence: 99%
“…A confocal Raman microscope records spectra from microscopic spatial regions within a sample. The objective brings the excitation beam to a tight, diffraction-limited spot (focal volume), and Raman scattered radiation is collected from the region through an aperture that restricts light from outside the focal volume from reaching the detector. The dimensions of the aperture and excitation beam focus define the primary location probed within the sample. This so-called confocal probe volume region typically occupies a few femtoliters in measurements that employ high-numerical-aperture (NA) oil-immersion objectives. ,, In recent years, confocal Raman microscopy has emerged as a unique and powerful tool for conducting rapid, sensitive chemical assays based on detection within individual high surface area chromatographic particles (cf., refs ). With the confocal probe volume positioned centrally within a particle, the analyte extracted into the pores can be easily quantified, label-free at subnanomole levels. The latest work, centered on studies of DNA hybridization, has demonstrated spectral subtraction as effective for enhancing sensitivity .…”
Section: Introductionmentioning
confidence: 99%